Analysis of Information Management Policies and Knowledge Management of Provincial Electricity Authority - Pethkong, Komsan; Phungke, Chutinun (Journal of Advanced Development in Engineering and Science, 2023)
The objective of this article is to analyze the information management policy of Department Business Development Information and Communication Technology, Provincial Electricity Authority (PEA), which defines the information technology master plan of PEA in Phase 3 from 2556 to 2560 in order to develop their ICT services. This master plan supports the strategy driving with good governance in the organization. This study focuses on the policy, strategy planning, program in management of information technology and operational plans that defines the issues in the analysis for 4 issues: 1) information policy, information management plan and information management organization; 2) information use, information needs and information seeking behavior; 3) knowledge management; and 4) ethical practices of information. It can be found that the master plan of ICT of PEA has managed the information technology to response the changes in technology, economy and society which are both of the opportunities and challenges of the organization. Moreover, the policy focuses on developing knowledgebased society. The personnel are the key mechanism to force by developing human capital and intellectual capital, making up the good relationship between staffs and the organization, and supporting the organizational learning culture and knowledge management continuously to lead the organization can maximize benefits from ICT to achieve in finance, customer care, and social and environmental sustainability.